Strategi Komunikasi B2B Sales Account Executive dalam Memperkuat Loyalitas Pelanggan Berbasis FRIO di PT PLN Nusantara Power - Putri Balqis Azzahra; Santoso, Hudi (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The Business-to-Business (B2B) communication strategy implemented by Sales Account Executives (SAEs) to increase customer loyalty uses the FRIO (Facts, Reasons, Impacts, Outcome) approach at PT PLN Nusantara Power. The background of this research arose due to the mismatch between the high level of customer satisfaction and the level of loyalty that has not reached optimal levels. This research uses a descriptive qualitative method by collecting data through interviews, observations, and document analysis. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions, and then categorized within the FRIO analysis framework. The results show that B2B communication conducted by SAEs is multichannel and flexible, and is very important in building trust and long-term relationships. The quality of information such as completeness and speed of data, remains a challenge that affects customer loyalty. This research confirms that effective communication is not only measured by its intensity, but also by the value of the information conveyed to support customer business decision making.